Regenerative Medicine Treatments for Androgenetic Alopecia - Venkataram Mysore; Sajin Alexander; Suman Nepal; Aniketh Venkataram (Indian Journal of Plastic Surgery)
Regenerative medicine and the role of stem cells are being studied for applications in nearly every field of medicine. The pluripotent nature of stem cells underlies their vast potential for treatment of androgenic alopecia. Several advances in recent years have heightened interest in this field, chief among them are the evolution of simpler techniques to isolate regenerative elements and stems cells. These techniques are easy, outpatient procedures with immediate injection, often single session with harvest, and minimal manipulation (usually physical). This paper seeks to critically review the existing data and determine the current evidence and their role in practice.